Delivering the promises of trait-based approaches to the needs of demographic approaches, and vice versa. - Salguero-Gómez, R; Violle, C; Gimenez, O; Childs, D (Wiley, 2018)
1. Few facets of biology vary more than functional traits and life‐history traits. To explore this vast variation, functional ecologists and population ecologists have developed independent approaches that identify the mechanisms behind and consequences of trait variation.